INCREASE OF CONTROL SURFACES EFFICIENCY OF A SUBSONIC AIRCRAFT OF SHORT TAKEOFF AND LANDING - Yu. S. Mikhailov (Научный вестник МГТУ ГА, 2019)
A steady growth of aviation transportation (4-5% per year) causes excessive saturation at numerous major airports. As a result, many flights are delayed. One of the ways to deal with this growing problem is to transfer regional propeller aircraft maintenance to suburban airports. It will require both a modernization of local airports and the design of a new generation of regional aircraft with short takeoff and landing (STOL). The aircraft ability to operate from short runways depends not only on wing unit loading and on high-lift capacities but also it is determined by the control surfaces efficiency. The latter often becomes one of the major reasons for limitation of the amount of lift used in STOL configuration. Thus, the successful application of high-lift devices stipulates the necessity for both the efficiency increasing of existing aircraft control surfaces and the development of some alternative form of lateral control not requiring a significant wingspan proportion. The forms of a lateral control, this article considers, include the interceptor, drooped ailerons, ailerons fitted with mini-flap and one of the alternative forms which uses differential flap section deflection. Several mini-flaps with a various chord are also considered to increase the available rudder yawing moment. The efficiency of the above-mentioned control surfaces has been studied in TsAGI low speed wind tunnel on a model of a twin-engine light aircraft with an enhanced level of lifting capacity on take-off and landing configurations. The tests were conducted at a Reynolds number of 1.0×106 and Mach number of 0.15.